Motivation Through Incentives: An Analysis of 20 Case Studiies from Contemporary Large Western Organizations - Najam, Ali Shakoor (2009)
This study looks at how the large western organizations have employed various incentive schemes and stimulating techniques to motivate employees within their organizations and how the concept of employee motivation has impacted their competitive position in the industry as well as the organizations internal culture. In carrying out the analysis, the study evaluates the evolution of motivation theories over time from the previously scientific management orientation to a more humanitarian approach. The study was conducted with the aid of a secondary research methodology that revealed that most techniques of motivation were incorporated in the performance evaluation system of the organization. Thus, the most commonly used techniques include variable pay structures and systems of performance related pay in view of achieving short and long term goals and targets. Such methods also include scheduled bonuses and promotion prospects, while performance evaluation methods in various organizations differ. In addition to short term monetary benefits, employees are often given stock options that motivate them through the incentive of having a say in the running of the business. The theoretical framework builds up on the mechanism of motivation allowing an analysis of how motivation schemes satisfy various needs of employees, encourage a nurturing environment and reducing the impact of any de-motivators in the organization culture. While many of these techniques enhance performance, the study also analyses failures of certain techniques that do not always prove to be efficient. This suggests that the choice of methods of motivation needs to be made carefully. How these programs are designed is therefore important and the research has suggested that this design should maintain a balance between monetary and non monetary factors while keeping in mind the long term cost efficiency.